ANALYSIS OF WORLD STANDARDS OF RISK MANAGEMENT IN THE CONTEXT OF IMPLEMENTATION OF AVIATION ACTIVITY - Alexeiev, Oleh; Volkogon, Viktoriia; Pechevystyi, Ruslan; Karapetian, Serob (Proceedings of National Aviation University (archive), 2019)
The article deals with the analysis of world standards of risk management. It is determined that due to the similarity of the nature of the risks, the relevance of their reduction to the minimum possible level has increased. The creation of the latest methodology for controlling the level of flight safety, for providing and supporting decision-making by the human operator, provides for the critical elements of the ATM system to control the level of risk.